Genetic ancestry of the Mulam ethnic group: admixture from ancient Yellow River, southern native, and Austronesian populations - Wendi Dang; Xiaoming Wu; Jing Zhao; Song Lin; Xirui Wang; Xiaomin Yang; Jin Sun; Tielin Yang; Chuan-Chao Wang; Hu-Qin Zhang (Human Genetics, 2026)

Identification of novel loci regulating circulating melatonin and its causal relationship with hypertension - Lin Yan; Yang Qiu; Zhiwen Mo; Mingli Li; Xueran Huang; Yongfen Gao; Boteng Yan; Qiantu Hu; Haiying Zhang; Zengnan Mo; Rui Lin (Human Genetics, 2026)

Human YTHDC2 mutations disturb RNA homeostasis of oocytes and early embryos - Wei Su; Yang Wang; Jiaqi Sun; Changlong Zhang; Changjian Yin; Ying Cui; Xiaolei Chen; Bohan Yang; Shigang Zhao; Keliang Wu; Ge Lin; Zi-Jiang Chen; et al. (Human Genetics, 2026)

Distinct regulatory elements of SLC6A14 expression contribute to modification of cystic fibrosis phenotypes - Mohsen Esmaeili; Cheng Wang; Fan Lin; Naim Panjwani; Adele Chan; Gengming He; Katherine Keenan; Julie Avolio; Ann Harris; Johanna M. Rommens; Lisa J. Strug (Human Genetics, 2026)

Novel biallelic LSS variants in autosomal recessive hypotrichosis simplex: insights from a multi-omics approach - Xiaxia Liu; Kai Liu; Yuda Wei; Yongzhen Qi; Yangyang Luo; Tingli Chen; Xiaohua Ye; Junxu Lu; Yunjia Li; Liangqian Jiang; Juan Teng; Xingzhu Geng; et al. (Human Genetics, 2026)

Exploratory analysis of HLA SNPs associated with occult HBV infection: a multicenter case–control study in Chinese blood donors - Lin Zhou; Ying Yan; Huimin Ji; Huizhen Sun; Zhuoqun Lu; Le Chang; Lunan Wang (Human Genetics, 2026)

Mendelian randomization analysis and molecular mechanism study of childhood asthma and obstructive sleep apnea - Xinyu Wang; Lin Zhang; Hao Chen; Ting Tian; Lulu Wu; Yuping Huang; Qian Cao; Lili Zhuang; Guoping Zhou (Human Genetics, 2025)

Decade-long application of preimplantation genetic testing for DMD/BMD: analysis of five clinical strategies and embryo recombination patterns - Weili Wang; Jing Dai; Xiao Hu; Wenbin He; Yifan Gu; Zhenxing Wan; Yi Zhang; Keli Luo; Wen Li; Qianjun Zhang; Fei Gong; Guangxiu Lu; et al. (Human Genetics, 2025)

Predicting the impact of rare variants on RNA splicing in CAGI6 - Jenny Lord; Carolina Jaramillo Oquendo; Htoo A. Wai; Andrew G. L. Douglas; David J. Bunyan; Yaqiong Wang; Zhiqiang Hu; Zishuo Zeng; Daniel Danis; Panagiotis Katsonis; Amanda Williams; Olivier Lichtarge; et al. (Human Genetics, 2025)
Variants which disrupt splicing are a frequent cause of rare disease that have been under-ascertained clinically. Accurate and efficient methods to predict a variant’s impact on splicing are needed to interpret the growing number of variants of unknown significance (VUS) identified by exome and genome sequencing. Here, we present the results of the CAGI6 Splicing VUS challenge, which invited predictions of the splicing impact of 56 variants ascertained clinically and functionally validated to determine splicing impact. The performance of 12 prediction methods, along with SpliceAI and CADD, was compared on the 56 functionally validated variants. The maximum accuracy achieved was 82% from two different approaches, one weighting SpliceAI scores by minor allele frequency, and one applying the recently published Splicing Prediction Pipeline (SPiP). SPiP performed optimally in terms of sensitivity, while an ensemble method combining multiple prediction tools and information from databases exceeded all others for specificity. Several challenge methods equalled or exceeded the performance of SpliceAI, with ultimate choice of prediction method likely to depend on experimental or clinical aims. One quarter of the variants were incorrectly predicted by at least 50% of the methods, highlighting the need for further improvements to splicing prediction methods for successful clinical application.

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

A methodology for gene level omics-WAS integration identifies genes influencing traits associated with cardiovascular risks: the Long Life Family Study - Sandeep Acharya; Shu Liao; Wooseok J. Jung; Yu S. Kang; Vaha Akbary Moghaddam; Mary F. Feitosa; Mary K. Wojczynski; Shiow Lin; Jason A. Anema; Karen Schwander; Jeff O. Connell; Michael A. Province; et al. (Human Genetics, 2024)
The Long Life Family Study (LLFS) enrolled 4953 participants in 539 pedigrees displaying exceptional longevity. To identify genetic mechanisms that affect cardiovascular risks in the LLFS population, we developed a multi-omics integration pipeline and applied it to 11 traits associated with cardiovascular risks. Using our pipeline, we aggregated gene-level statistics from rare-variant analysis, GWAS, and gene expression-trait association by Correlated Meta-Analysis (CMA). Across all traits, CMA identified 64 significant genes after Bonferroni correction (p ≤ 2.8 × 10 –7 ), 29 of which replicated in the Framingham Heart Study (FHS) cohort. Notably, 20 of the 29 replicated genes do not have a previously known trait-associated variant in the GWAS Catalog within 50 kb. Thirteen modules in Protein–Protein Interaction (PPI) networks are significantly enriched in genes with low meta-analysis p-values for at least one trait, three of which are replicated in the FHS cohort. The functional annotation of genes in these modules showed a significant over-representation of trait-related biological processes including sterol transport, protein-lipid complex remodeling, and immune response regulation. Among major findings, our results suggest a role of triglyceride-associated and mast-cell functional genes FCER1A , MS4A2 , GATA2 , HDC , and HRH4 in atherosclerosis risks. Our findings also suggest that lower expression of ATG2A , a gene we found to be associated with BMI, may be both a cause and consequence of obesity. Finally, our results suggest that ENPP3 may play an intermediary role in triglyceride-induced inflammation. Our pipeline is freely available and implemented in the Nextflow workflow language, making it easily runnable on any compute platform ( https://nf-co.re/omicsgenetraitassociation ) .

Phenotypic and genetic effect of carotid intima-media thickness on the risk of stroke - Wenqiang Zhang; Jingwei Zhu; Xuan Wu; Tianle Feng; Wei Liao; Xuan Li; Jianci Chen; Li Zhang; Chenghan Xiao; Huijie Cui; Chao Yang; Peijing Yan; et al. (Human Genetics, 2024)

Plasma-derived exosomal miRNA profiles reveal potential epigenetic pathogenesis of premature ovarian failure - Jiaqiong Lin; Zhihong Wu; Yingchun Zheng; Zongrui Shen; Zhongzhi Gan; Shunfei Ma; Yanhui Liu; Fu Xiong (Human Genetics, 2024)

N6-methyladenosine modified lncRNAs signature for stratification of biochemical recurrence in prostate cancer - Yingke Liang; Wenjun Yin; Zhouda Cai; Hongwei Luo; Qinwei Liu; Chuanfan Zhong; Jiahong Chen; Zhuoyuan Lin; Yaqiang Huang; Zhenguo Liang; Junhong Deng; Weide Zhong; et al. (Human Genetics, 2024)

Genome-wide DNA methylation of lesional and peri-lesional skin in vitiligo: a comparative and integrated analysis of multi-omics in Chinese population - Lin Liu; Yuzhou Xue; Yuxin Li; Yangmei Chen; Xingyu Pan; Yujing Huang; Tingqiao Chen; Judan Zhong; Xinyi Shao; Yihuan Pu; Jin Chen (Human Genetics, 2024)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Homozygous variants in CDC23 cause female infertility characterized by oocyte maturation defects - Huizhen Fan; Zhou Zhou; Wei Zheng; Yichun Guan; Qingxia Meng; Wenjing Wang; Jie Dong; Liuxia Wan; Jiawei Zhu; Yang Zeng; Ruyi Liu; Hao Gu; et al. (Human Genetics, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

TMEM151A variants associated with paroxysmal kinesigenic dyskinesia - Hua lin Huang; Qing xia Zhang; Fei Huang; Xiao yan Long; Zhi Song; Bo Xiao; Guo liang Li; Cai yu Ma; Ding Liu (Human Genetics, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Locus-level antagonistic selection shaped the polygenic architecture of human complex diseases - Weichen Song; Kai Yuan; Zhe Liu; Wenxiang Cai; Jue Chen; Shunying Yu; Min Zhao; Guan Ning Lin (Human Genetics, 2022)

GATA4 and estrogen receptor alpha bind at SNPs rs9921222 and rs10794639 to regulate AXIN1 expression in osteoblasts - Sarocha Suthon; Rachel S. Perkins; Jianjian Lin; John R. Crockarell; Gustavo A. Miranda-Carboni; Susan A. Krum (Human Genetics, 2022)

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

Correction to: Shared genetic architecture between metabolic traits and Alzheimer’s disease: a large-scale genome-wide cross-trait analysis - Zhaozhong Zhu; Yifei Lin; Xihao Li; Jane A. Driver; Liming Liang (Human Genetics, 2021)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Optimized trio genome sequencing (OTGS) as a first-tier genetic test in critically ill infants: practice in China - Huijun Wang; Yulan Lu; Xinran Dong; Guoping Lu; Guoqiang Cheng; Yanyan Qian; Qi Ni; Ping Zhang; Lin Yang; Bingbing Wu; Wenhao Zhou (Human Genetics, 2020)

Novel mutations in SPEF2 causing different defects between flagella and cilia bridge: the phenotypic link between MMAF and PCD - Chaofeng Tu; Hongchuan Nie; Lanlan Meng; Weili Wang; Haiyu Li; Shimin Yuan; Dehua Cheng; Wenbin He; Gang Liu; Juan Du; Fei Gong; Guangxiu Lu; et al. (Human Genetics, 2020)

High-throughput transcriptome analysis reveals that the loss of Pten activates a novel NKX6-1/RASGRP1 regulatory module to rescue microphthalmia caused by Fgfr2-deficient lenses - Stephanie L. Padula; Deepti Anand; Thanh V. Hoang; Blake R. Chaffee; Lin Liu; Chun Liang; Salil A. Lachke; Michael L. Robinson (Human Genetics, 2019)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Shared genetic architecture between metabolic traits and Alzheimer’s disease: a large-scale genome-wide cross-trait analysis - Zhaozhong Zhu; Yifei Lin; Xihao Li; Jane A. Driver; Liming Liang (Human Genetics, 2019)

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease - Jiaqi Liu; Yangzhong Zhou; Sen Liu; Xiaofei Song; Xin-Zhuang Yang; Yanhui Fan; Weisheng Chen; Zeynep Coban Akdemir; Zihui Yan; Yuzhi Zuo; Renqian Du; Zhenlei Liu; et al. (Human Genetics, 2018)

Genotype imputation for Han Chinese population using Haplotype Reference Consortium as reference - Yuan Lin; Lu Liu; Sen Yang; Yun Li; Dongxin Lin; Xuejun Zhang; Xianyong Yin (Human Genetics, 2018)

regSNPs-splicing: a tool for prioritizing synonymous single-nucleotide substitution - Xinjun Zhang; Meng Li; Hai Lin; Xi Rao; Weixing Feng; Yuedong Yang; Matthew Mort; David N. Cooper; Yue Wang; Yadong Wang; Clark Wells; Yaoqi Zhou; et al. (Human Genetics, 2017)

A cis-eQTL genetic variant of the cancer–testis gene CCDC116 is associated with risk of multiple cancers - Na Qin; Cheng Wang; Qun Lu; Tongtong Huang; Meng Zhu; Lihua Wang; Fei Yu; Mingtao Huang; Yue Jiang; Juncheng Dai; Hongxia Ma; Guangfu Jin; et al. (Human Genetics, 2017)

Regulatory element-based prediction identifies new susceptibility regulatory variants for osteoporosis - Shi Yao; Yan Guo; Shan-Shan Dong; Ruo-Han Hao; Xiao-Feng Chen; Yi-Xiao Chen; Jia-Bin Chen; Qing Tian; Hong-Wen Deng; Tie-Lin Yang (Human Genetics, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Identification of susceptibility gene associated with female primary Sjögren’s syndrome in Han Chinese by genome-wide association study - I-Wen Song; Hsiang-Cheng Chen; Yuh-Feng Lin; Jenn-Hwai Yang; Chi-Ching Chang; Chung-Tei Chou; Ming-Ta Michael Lee; Yi-Chun Chou; Chien-Hsiun Chen; Yuan-Tsong Chen; Chen-Hung Chen; Jer-Yuarn Wu (Human Genetics, 2016)

FUS-linked essential tremor associated with motor dysfunction in Drosophila - Murni Tio; Rujing Wen; Yih Lin Lim; Huashan Wang; Shuo-Chien Ling; Yi Zhao; Eng-King Tan (Human Genetics, 2016)

Resolving the ancestry of Austronesian-speaking populations - Pedro A. Soares; Jean A. Trejaut; Teresa Rito; Bruno Cavadas; Catherine Hill; Ken Khong Eng; Maru Mormina; Andreia Brandão; Ross M. Fraser; Tse-Yi Wang; Jun-Hun Loo; Christopher Snell; et al. (Human Genetics, 2016)

A new method for estimating effect size distribution and heritability from genome-wide association summary results - Lei Zhang; Yue-Ping Shen; Wen-Zhu Hu; Shu Ran; Yong Lin; Shu-Feng Lei; Yong-Hong Zhang; Christopher J. Papasian; Nengjun Yi; Yu-Fang Pei (Human Genetics, 2016)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Unraveling the complex genetic model for cystic fibrosis: pleiotropic effects of modifier genes on early cystic fibrosis-related morbidities - Weili Li; David Soave; Melissa R. Miller; Katherine Keenan; Fan Lin; Jiafen Gong; Theodore Chiang; Anne L. Stephenson; Peter Durie; Johanna Rommens; Lei Sun; Lisa J. Strug (Human Genetics, 2014)

WNT10A variants are associated with non-syndromic tooth agenesis in the general population - Shujuan Song; Ruiying Zhao; Huiying He; Jin Zhang; Hailan Feng; Liyun Lin (Human Genetics, 2014)

A functional variant of pre-miRNA-196a2 confers risk for Behcet’s disease but not for Vogt–Koyanagi–Harada syndrome or AAU in ankylosing spondylitis - Jian Qi; Shengping Hou; Qi Zhang; Dan Liao; Lin Wei; Jing Fang; Yan Zhou; Aize Kijlstra; Peizeng Yang (Human Genetics, 2013)

Responses to booster hepatitis B vaccination are significantly correlated with genotypes of human leukocyte antigen (HLA)-DPB1 in neonatally vaccinated adolescents - Tzu-Wei Wu; Chen-Chung Chu; Tzu-Ying Ho; Huei-Wen Chang Liao; Sheng-Kai Lin; Marie Lin; Hans Hsienhong Lin; Li-Yu Wang (Human Genetics, 2013)

Genetic variants at 4q21, 4q23 and 12q24 are associated with esophageal squamous cell carcinoma risk in a Chinese population - Yong Gao; Yisha He; Jing Xu; Lin Xu; Jiangbo Du; Chen Zhu; Haiyong Gu; Hongxia Ma; Zhibin Hu; Guangfu Jin; Xiaofei Chen; Hongbing Shen (Human Genetics, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Identification of genetic associations of SP110/MYBBP1A/RELA with pulmonary tuberculosis in the Chinese Han population - Lei Cai; Shao-Li Deng; Li Liang; Hui Pan; Jia Zhou; Mei-Yan Wang; Jun Yue; Chun-Ling Wan; Guang He; Lin He (Human Genetics, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Cathepsin B SNPs elevate the pathological development of oral cancer and raise the susceptibility to carcinogen-mediated oral cancer - Mu-Kuan Chen; Shih-Chi Su; Chiao-Wen Lin; Chiung-Man Tsai; Shun-Fa Yang; Chia-Jui Weng (Human Genetics, 2012)

Coexisting mutations/polymorphisms of the long QT syndrome genes in patients with repaired Tetralogy of Fallot are associated with the risks of life-threatening events - Shuenn-Nan Chiu; Mei-Hwan Wu; Ming-Jai Su; Jou-Kou Wang; Ming-Tai Lin; Chien-Chih Chang; Hui-Wen Hsu; Ching-Tsuen Shen; Olivier Thériault; Mohamed Chahine (Human Genetics, 2012)

Erratum to: Association between gout and polymorphisms in GCKR in male Han Chinese - Jing Wang; Shiguo Liu; Binbin Wang; Zhimin Miao; Lin Han; Nan Chu; Kun Zhang; Dongmei Meng; Changgui Li; Xu Ma (Human Genetics, 2012)

Association between gout and polymorphisms in GCKR in male Han Chinese - Jing Wang; Shiguo Liu; Binbin Wang; Zhimin Miao; Lin Han; Nan Chu; Kun Zhang; Dongmei Meng; Changgui Li; Xu Ma (Human Genetics, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

The human lactase persistence-associated SNP −13910*T enables in vivo functional persistence of lactase promoter–reporter transgene expression - Lin Fang; Jong Kun Ahn; Dariusz Wodziak; Eric Sibley (Human Genetics, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Associations between common variants in GC and DHCR7/NADSYN1 and vitamin D concentration in Chinese Hans - Ling Lu; Hongguang Sheng; Huaixing Li; Wei Gan; Chen Liu; Jingwen Zhu; Ruth J. F. Loos; Xu Lin (Human Genetics, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Genome-wide association study identifies HMGN3 locus for spine bone size variation in Chinese - Shu-Feng Lei; Hui Shen; Tie-Lin Yang; Yan Guo; Shan-Shan Dong; Xiang-Hong Xu; Fei-Yan Deng; Qing Tian; Yong-Jun Liu; Yao-Zhong Liu; Jian Li; Hong-Wen Deng (Human Genetics, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Molecular genetic studies of gene identification for sarcopenia - Li-Jun Tan; Shan-Lin Liu; Shu-Feng Lei; Christopher J. Papasian; Hong-Wen Deng (Human Genetics, 2012)

Novel variant Pro143Ala in HTRA2 contributes to Parkinson’s disease by inducing hyperphosphorylation of HTRA2 protein in mitochondria - Chin-Hsien Lin; Meng-Ling Chen; Grace Shiahuy Chen; Chun-Hwei Tai; Ruey-Meei Wu (Human Genetics, 2011)

Common genetic variation in the 3′-untranslated region of gonadotropin-releasing hormone receptor regulates gene expression in cella and is associated with thyroid function, insulin secretion as well as insulin sensitivity in polycystic ovary syndrome patients - Qiaoli Li; Guizhong Yang; Ying Wang; Xiaoping Zhang; Qing Sang; Huan Wang; Xinzhi Zhao; Qinghe Xing; Lin He; Lei Wang (Human Genetics, 2011)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Prospective variants screening of connexin genes in children with hearing impairment: genotype/phenotype correlation - Jiann-Jou Yang; Wen-Hung Wang; Yen-Chun Lin; Hsu-Huei Weng; Jen-Tsung Yang; Chung-Feng Hwang; Che-Min Wu; Shuan-Yow Li (Human Genetics, 2010)

The CAG repeat in SCA12 functions as a cis element to up-regulate PPP2R2B expression - Chih-Hsin Lin; Chiung-Mei Chen; Yi-Ting Hou; Yih-Ru Wu; Hsiu-Mei Hsieh-Li; Ming-Tsan Su; Guey-Jen Lee-Chen (Human Genetics, 2010)

WRN mutations in Werner syndrome patients: genomic rearrangements, unusual intronic mutations and ethnic-specific alterations - Katrin Friedrich; Lin Lee; Dru F. Leistritz; Gudrun Nürnberg; Bidisha Saha; Fuki M. Hisama; Daniel K. Eyman; Davor Lessel; Peter Nürnberg; Chumei Li; María J. Garcia-F-Villalta; Carolien M. Kets; et al. (Human Genetics, 2010)

Erratum to: Novel mutations in the connexin43 (GJA1) and GJA1 pseudogene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Jia-Ching Shieh; Mei-Ling Lin; Shuan-Yow Li (Human Genetics, 2010)

A meta-analysis of three polymorphisms in the endothelial nitric oxide synthase gene (NOS3) and their effect on the risk of diabetic nephropathy - Zhen Zeng; Lina Li; Zhao Zhang; Yang Li; Zhiyun Wei; Ke Huang; Lin He; Yongyong Shi (Human Genetics, 2010)

Genetic analysis of ABCG2 gene C421A polymorphism with gout disease in Chinese Han male population - Binbin Wang; Zhimin Miao; Shiguo Liu; Jing Wang; Shiyi Zhou; Lin Han; Dongmei Meng; Yunlong Wang; Changgui Li; Xu Ma (Human Genetics, 2010)

Monoamine oxidase A gene polymorphisms and enzyme activity associated with risk of gout in Taiwan aborigines - Hung-Pin Tu; Albert Min-Shan Ko; Shu-Jung Wang; Chien-Hung Lee; Rod A. Lea; Shang-Lun Chiang; Hung-Che Chiang; Tsu-Nai Wang; Meng-Chuan Huang; Tsan-Teng Ou; Gau-Tyan Lin; Ying-Chin Ko (Human Genetics, 2010)

Modifier gene study of meconium ileus in cystic fibrosis: statistical considerations and gene mapping results - Ruslan Dorfman; Weili Li; Lei Sun; Fan Lin; Yongqian Wang; Andrew Sandford; Peter D. Paré; Karen McKay; Hana Kayserova; Tereza Piskackova; Milan Macek; Kamila Czerska; et al. (Human Genetics, 2009)

Non-synonymous GIGYF2 variants in Parkinson’s disease from two Asian populations - Eng-King Tan; Chin-Hslen Lin; Chun-Hwei Tai; Louis C. Tan; Meng-Ling Chen; R. Li; Hui-Qin Lim; Ratnagopal Pavanni; Yih Yuen; K. M. Prakash; Yi Zhao; Ruey-Meei Wu (Human Genetics, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Ataxia and pancytopenia caused by a mutation in TINF2 - Elena Tsangaris; Sally-Lin Adams; Grace Yoon; David Chitayat; Peter Lansdorp; Inderjeet Dokal; Yigal Dror (Human Genetics, 2008)

A novel genetic locus for familial febrile seizures and epilepsy on chromosome 3q26.2–q26.33 - Xiao-Hua Dai; Wen-Wu Chen; Xu Wang; Qi-Hui Zhu; Cong Li; Lin Li; Mu-Gen Liu; Qing-K. Wang; Jing-Yu Liu (Human Genetics, 2008)

Functional characterization of the human TPH2 5′ regulatory region: untranslated region and polymorphisms modulate gene expression in vitro - Guo-Lin Chen; Eric J. Vallender; Gregory M. Miller (Human Genetics, 2008)

Positive association between OLIG2 and schizophrenia in the Chinese Han population - Ke Huang; Wei Tang; Ruqi Tang; Zhao Xu; Zhangdong He; Zhiqiang Li; Yifeng Xu; Xingwang Li; Guang He; Guoying Feng; Lin He; YongYong Shi (Human Genetics, 2008)

Association analysis of SOD2 variants with methamphetamine psychosis in Japanese and Taiwanese populations - Kazuhiko Nakamura; Chih-Ken Chen; Yoshimoto Sekine; Yasuhide Iwata; A. Anitha; El-Wui Loh; Nori Takei; Atsuko Suzuki; Masayoshi Kawai; Kiyokazu Takebayashi; Katsuaki Suzuki; Yoshio Minabe; et al. (Human Genetics, 2006)

Phenotypic characterization of Bbs4 null mice reveals age-dependent penetrance and variable expressivity - Erica R. Eichers; Muhammad M. Abd-El-Barr; Richard Paylor; Richard Alan Lewis; Weimin Bi; Xiaodi Lin; Thomas P. Meehan; David W. Stockton; Samuel M. Wu; Elizabeth Lindsay; Monica J. Justice; Philip L. Beales; et al. (Human Genetics, 2006)

Meta-analysis shows association between the tryptophan hydroxylase (TPH) gene and schizophrenia - Dawei Li; Lin He (Human Genetics, 2006)

Association analyses of CYP19 gene polymorphisms with height variation in a large sample of Caucasian nuclear families - Tie-Lin Yang; Dong-Hai Xiong; Yan Guo; Robert R. Recker; Hong-Wen Deng (Human Genetics, 2006)

Structure and function of glucose-6-phosphate dehydrogenase-deficient variants in Chinese population - Weiying Jiang; Guolong Yu; Peng Liu; Qian Geng; Luming Chen; Qundi Lin; Xiaoqin Ren; Wenhong Ye; Yongshu He; Yibin Guo; Shan Duan; Jing Wen; et al. (Human Genetics, 2006)

Further clarification of the contribution of the tryptophan hydroxylase (TPH) gene to suicidal behavior using systematic allelic and genotypic meta-analyses - Dawei Li; Lin He (Human Genetics, 2006)

Functional polymorphisms of FGA, encoding α fibrinogen, are associated with susceptibility to venous thromboembolism in a Taiwanese population - Yu-Lin Ko; Lung-An Hsu; Tsu-Shiu Hsu; Chia-Ti Tsai; Ming-Sheng Teng; Semon Wu; Chi-Jen Chang; Ying-Shiung Lee (Human Genetics, 2006)

Phylogenetic relationship of the populations within and around Japan using 105 short tandem repeat polymorphic loci - Shi-Lin Li; Toshimichi Yamamoto; Takashi Yoshimoto; Rieko Uchihi; Masaki Mizutani; Yukihide Kurimoto; Katsushi Tokunaga; Feng Jin; Yoshinao Katsumata; Naruya Saitou (Human Genetics, 2006)

A locus for familial generalized lentiginosis without systemic involvement maps to chromosome 4q21.1–q22.3 - Qinghe Xing; Xiangdong Chen; Mingtai Wang; Wenjie Bai; Xin Peng; Rui Gao; Shengnan Wu; Xueqing Qian; Wei Qin; Jianjun Gao; Guoyin Feng; Lin He (Human Genetics, 2005)

Characterization of Usher syndrome type I gene mutations in an Usher syndrome patient population - Xiao Mei Ouyang; Denise Yan; Li Lin Du; J. Fielding. Hejtmancik; Samuel G. Jacobson; Walter E. Nance; An Ren Li; Simon Angeli; Muriel Kaiser; Valerie Newton; Steve D. M. Brown; Thomas Balkany; et al. (Human Genetics, 2005)

Expression studies of mutations underlying Taiwanese Hunter syndrome (mucopolysaccharidosis type II) - Jui-Hung Chang; Shuan-Pei Lin; Shu-Chuan Lin; Kai-Li Tseng; Chia-Ling Li; Chih-Kuang Chuang; Guey-Jen Lee-Chen (Human Genetics, 2005)

Localized aggressive periodontitis is linked to human chromosome 1q25 - Yefu Li; Lin Xu; Hatice Hasturk; Alpdogan Kantarci; Steven R. DePalma; Thomas E. Van Dyke (Human Genetics, 2004)

A novel missense mutation in the paired domain of PAX9 causes non-syndromic oligodontia - Dolrudee Jumlongras; Jenn-Yih Lin; Anas Chapra; Christine E. Seidman; Jonathan G. Seidman; Richard L. Maas; Bjorn R. Olsen (Human Genetics, 2004)

Analysis of heat-shock protein70 gene polymorphisms and the risk of Parkinson?s disease - Chiung-Mei Chen; Yuying Hsu; Sih-Jing Lin; Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Cheng-Kuang Wang; Yi-Ying Lin; Yih-Ru Wu; Hon-Chung Fung (Human Genetics, 2004)

A deletion mutation in the ?A1/A3 crystallin gene (CRYBA1/A3) is associated with autosomal dominant congenital nuclear cataract in a Chinese family - Yanhua Qi; Hongyan Jia; Shangzhi Huang; Hui Lin; Jingzhi Gu; Hong Su; Tieying Zhang; Ya Gao; Lijun Qu; Dandan Li; Ying Li (Human Genetics, 2004)

Excavating Y-chromosome haplotype strata in Anatolia - Cengiz Cinnioglu; Roy King; Toomas Kivisild; Ersi Kalfoglu; Sevil Atasoy; Gianpiero L. Cavalleri; Anita S. Lillie; Charles C. Roseman; Alice A. Lin; Kristina Prince; Peter J. Oefner; Peidong Shen; et al. (Human Genetics, 2004)

Evidence of a founder effect for the 235delC mutation of GJB2 (connexin26) in east Asians - Denise Yan; Hong-Joon Park; Xiao Mei Ouyang; Arti Pandya; Katsumi Doi; Raadnabazar Erdenetungalag; Li Lin Du; Naoki Matsushiro; Walter E. Nance; Andrew J. Griffith; Xue Zhong Liu (Human Genetics, 2003)

Surfactant proteinA and B genetic variants predispose to idiopathic pulmonary fibrosis - Moises Selman; Hung-Mo Lin; Martha Montao; Audrey L. Jenkins; Andrea Estrada; Zhenwu Lin; Guirong Wang; Susan L. DiAngelo; Xiaoxuan Guo; Todd M. Umstead; C. Max Lang; Annie Pardo; et al. (Human Genetics, 2003)

Novel mutations in the IRF6 gene for Van der Woude syndrome - Xiaofang Wang; Jiali Liu; Haibing Zhang; Mingzhen Xiao; Jinfeng Li; Chunling Yang; Xianjun Lin; Zizhong Wu; Landian Hu; Xiangyin Kong (Human Genetics, 2003)

A common IL-13 Arg130Gln single nucleotide polymorphism among Chinese atopy patients with allergic rhinitis - Min Wang; Zhi-Min Xing; Chao Lu; You-Xiang Ma; De-Lin Yu; Zheng Yan; Shen-Wu Wang; Li-Sheng Yu (Human Genetics, 2003)

Microsatellite polymorphism in promoter of heme oxygenase-1 gene is associated with susceptibility to coronary artery disease in type 2 diabetic patients - Ying-Hwa Chen; Shing-Jong Lin; Ming-Wei Lin; Hui-Ling Tsai; San-San Kuo; Jaw-Wen Chen; Min-Ji Charng; Tao-Cheng Wu; Lung-Ching Chen; Philip Ding; Wen-Harn Pan; Yuh-Shan Jou; et al. (Human Genetics, 2002)

Allelic and locus heterogeneity in autosomal recessive gelatinous drop-like corneal dystrophy - Zhaoxia Ren; Pei-Yu Lin; Gordon K. Klintworth; Fumino Iwata; Francis L. Munier; Daniel F. Schorderet; Leila El Matri; Veena Theendakara; Surendra Basti; Madhukar Reddy; Fielding J. Hejtmancik (Human Genetics, 2002)

Genetic variations in the cholesteryl ester transfer protein gene and high density lipoprotein cholesterol levels in Taiwanese Chinese - Lung-An Hsu; Yu-Lin Ko; Kuang-Hung Hsu; Yu-Hsien Ko; Ying-Shiung Lee (Human Genetics, 2002)

Distribution of glucose-6-phosphate dehydrogenase mutations in Southeast Asia - Kuni Iwai; Akira Hirono; Hiroyuki Matsuoka; Fumihiko Kawamoto; Toru Horie; Khin Lin; Indah S. Tantular; Yoes P. Dachlan; Harsono Notopuro; Noor I. Hidayah; Abdul M. Salim; Hisaichi Fujii; et al. (Human Genetics, 2001)

Human variant glucose-6-phosphate transporter is active in microsomal transport - Baochuan Lin; Chi-Jiunn Pan; Janice Chou (Human Genetics, 2000)

Autosomal dominant macrothrombocytopenia with leukocyte inclusions (May-Hegglin anomaly) is linked to chromosome 22q12-13 - Michael J. Kelley; William Jawien; Albert Lin; Karen Hoffmeister; Elizabeth W. Pugh; Kimberly F. Doheny; Jeannette F. Korczak (Human Genetics, 2000)

Autosomal dominant macrothrombocytopenia with leukocyte inclusions (May-Hegglin anomaly) is linked to chromosome 22q12-13 - Michael J. Kelley; William Jawien; Albert Lin; Karen Hoffmeister; Elizabeth W. Pugh; Kimberly F. Doheny; Jeannette F. Korczak (Human Genetics, 2000)

Type-1c glycogen storage disease is not caused by mutations in the glucose-6-phosphate transporter gene - B. Lin; H. Hiraiwa; C.-J. Pan; R.C. Nordlie; J.Y. Chou (Human Genetics, 1999)

Type-1c glycogen storage disease is not caused by mutations in the glucose-6-phosphate transporter gene - B. Lin; H. Hiraiwa; C.-J. Pan; R.C. Nordlie; J.Y. Chou (Human Genetics, 1999)

A novel mutation of the doublecortin gene in Japanese patients with X-linked lissencephaly and subcortical band heterotopia - M. Kato; Toshiyuki Kimura; Changqing Lin; Aiko Ito; Soichi Kodama; Tateki Morikawa; Takashi Soga; Kiyoshi Hayasaka (Human Genetics, 1999)

The spectrum of microsatellite loci on chromosomes 7 and 8 in Taiwan aboriginal populations: a comparative population genetic study - Chi-Chen Wei; Fu-Tien Chiang; Kuo-Sin Lin; L.-I. Lin (Human Genetics, 1999)

Familial clustering of rheumatoid arthritis with other autoimmune diseases - Jing-Ping Lin; Joseph M. Cash; Sharon Z. Doyle; Sandra Peden; Keith Kanik; Chris I. Amos; S. J. Bale; Ronald L. Wilder (Human Genetics, 1998)

Molecular analysis of survival motor neuron (SMN) and neuronal apoptosis inhibitory protein (NAIP) genes of spinal muscular atrophy patients and their parents - J.-G. Chang; Yuh-Jyh Jong; Shuan-Pei Lin; Bing-Wen Soong; Chang-Hai Tsai; T.-Y. Yang; Chih-Peng Chang; Wen-Shin Wang (Human Genetics, 1997)

Human centromeric DNAs - C. Lee; R. Wevrick; R. B. Fisher; M. A. Ferguson-Smith; C. C. Lin (Human Genetics, 1997)

Fine mapping of the MLK-3 gene within 11q13 and its exclusion as the MEN1 susceptibility gene - N. J. Lassam; Zheng Lin; Michael G. Shennan; Anouk Courseaux; Bin T. Teh; Patrick Gaudray; Catharina Larsson (Human Genetics, 1997)

Suggestive evidence for linkage of schizophrenia to markers on chromosome 13 in Caucasian but not Oriental populations - M.-W. Lin; P. Sham; Hai-Gwo Hwu; David Collier; Robin Murray; John F. Powell (Human Genetics, 1997)

Rapid detection of trisomy 21 by homologous gene quantitative PCR (HGQ-PCR) - Hsien-Hsiung Lee; Jan-Gowth Chang; Shuan-Pei Lin; Hsiang-Tai Chao; M.-L. Yang; Heung-Tat Ng (Human Genetics, 1997)

Somatic mosaicism for deletion of the entire NF1 gene identified by FISH - Bai-Lin Wu; Richard G. Boles; Hana Yaari; Stanislawa Weremowicz; Gretchen H. Schneider; B. R. Korf (Human Genetics, 1997)